2009
DOI: 10.7887/jcns.18.458
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Clinical Course after Carotid Artery Stenting using a Filter Device: A Case Report

Abstract: : Carotid artery stenting (CAS)for severe internal carotid artery stenosis has recently been intro − duced as an a】 ternative to carotid endarterectomy . Here , we present an unusual clinical course of a patient after CAS using the Angioguard filter device . Case : We present the case of a 75 − year − 01d 皿 an who suffered f め m cerebral infarctiQn in the left thalalnus . Three − dinlensional computed tomography confirmed asymptomatic stenosis (83%)in the lef し internal carotid arter ¥ Carotid artery stenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Tanaka et al 18) reported a patient in whom cerebral ischemic symptoms were more prominent than debris embolism on MRI after CAS; however, complete recovery was achieved. Regarding thromboembolism after CAS, Ishibashi et al 19) examined four patients with reversible cerebral ischemic complications a few hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al 18) reported a patient in whom cerebral ischemic symptoms were more prominent than debris embolism on MRI after CAS; however, complete recovery was achieved. Regarding thromboembolism after CAS, Ishibashi et al 19) examined four patients with reversible cerebral ischemic complications a few hours after surgery.…”
Section: Discussionmentioning
confidence: 99%